Development of Cooperatives in Increasing Cooperative Business (JEM17: Jurnal Ekonomi Manajemen, 2023)
The existence of cooperative units, both in the wider community and in private and government institutions or agencies, is very much needed and contributes significantly to its members in meeting their needs and economic activities. In order for cooperative units to maintain their existence and continue to develop, supporting rules and policies are needed, professional and optimal management as well as active and maximum member participation. This research is of a qualitative type, which aims to provide an overview of what factors influence the development of cooperatives to increase business in cooperatives in Mojokerto City. The sampling procedure in a survey is representative of the population. The basis for taking samples for surveys can be divided into at least three, namely systematic, random, or purposive sampling. The population in this study are all cooperatives in the administrative area of Mojokerto City in 2021. The total population is 175 cooperatives. The sampling technique used in this study was Stratified Random Sampling. Stratified random sampling was carried out because the population was not homogeneous. The development of cooperatives in the City of Mojokerto seen from membership has increased the number of members. This is very beneficial, because one of the indicators for the advancement of cooperatives is that more and more people become members of cooperatives. The Municipal Government of Mojokerto through the Office of Cooperatives & UKM has carried out coaching aimed at increasing cooperative business and strengthening cooperative institutions so that cooperatives function according to their objectives. Keywords: Work Ability, Coordination, Work Environment and Performance.